Analisis Penurunan Kadar TSS, COD Dan BOD Pada Limbah Cair RSUD Mgr. Gabriel Manek, SVD Atambua Nusa Tenggara Timur Dengan Metode Elektrolisis - Ledoh, Sherlly M. F.; Bere, Dau D.; Darmakusuma, Dodi D.; Lerrick, Reinner Ishaq (Universitas Nusa Cendana, 2022)
A research on waste water treatment using electrolysis has been carried out. The purpose of this study was to determine the optimum condition of electric voltage or time in reducing the Total Suspended Solid (TSS), Chemical Oxygen Demand (COD) and Biochemical Oxygent Demand (BOD) of Mgr. Gabriel Manek, SVD hospitall’s waste effluent. The method used in this study was carbon-carbon electrolysis method. The results showed decreasing of TSS levels from 2880 mg/L to 40 mg/L with % removal of 98.61%, COD levels from 8,240 mg/L to 2,883 mg/L with % removal of 65.34% and BOD levels of 520 mg/L to 40 mg/L with a % removal of 92.30%.